Preparation method of dry-method pole piece, dry-method pole piece and secondary battery
By using agitation and mixing of graphite, conductive carbon and auxiliary binder in the preparation of dry electrode sheet, adding PTFE and performing low-temperature stirring and heating fibrosis, the problem of poor wetting of dry electrodes is solved, and the wetting performance of the electrode sheet and the overall performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411737050.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The dry electrode has poor wetting properties in the electrolyte, which leads to the hindering of the liquid injection process of the battery and is difficult to improve.
A new dry electrode sheet preparation method is adopted, by stirring and mixing graphite, conductive carbon and auxiliary binder, adding the main binder PTFE, stirring under low temperature conditions, then heating and fibrosis treatment, and finally forming a dry electrode sheet by a hot rolling mill roll.
It significantly improves the wetting performance of the electrode sheet, improves the liquid injection process of the battery in the electrolyte, and improves the overall performance of the battery.
Smart Images

Figure CN119542361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of full lithium ion batteries, and in particular to a method for preparing a dry-process electrode, a dry-process electrode, and a secondary battery. Background Art
[0002] For the manufacturing process of lithium battery cells, the key performance of the cells mainly depends on the manufacturing process of the electrode sheets. At present, the manufacturing of electrode sheets is mainly divided into two types: wet method and dry method, and the wet process is the mainstream. The disadvantage of this process method is that toxic and expensive organic solvents such as N, N-dimethylpyrrolidone (NMP) are usually used. During the manufacturing process, NMP will cause the battery to swell during the cycle and the performance will decay too quickly due to excessive water content. In addition, the evaporation and recovery of solvents during the manufacturing process will also cause huge energy consumption. Based on the above problems, the development of solvent-free manufacturing methods for cost-effective and environmentally friendly lithium batteries has important research significance.
[0003] However, there are some urgent problems that need to be solved in dry-process electrodes, such as the problem of electrolyte wettability: CMC, SBR, PAA, etc. are commonly used binders for traditional wet-process electrodes. The above binders are all infiltrated and swelled in the electrolyte, especially SBR, which can swell by more than 200%. Due to the special production requirements of dry-process electrodes, PTFE is currently used as a binder, but this binder has excellent chemical resistance, so it is almost insoluble in the electrolyte, which poses great resistance to the subsequent processes of dry-process battery wetting and injection. Even after adding unmodified PVDF, its swelling rate can only reach about 40-50%, and the problem of poor wettability of dry-process batteries is still difficult to improve.
[0004] Therefore, there is an urgent need for a method to improve the wettability of dry electrodes. Summary of the invention
[0005] In order to solve the problem that the dry electrode in the above-mentioned background technology causes great resistance to the processes such as wetting and injection, the present invention provides the following technical solutions:
[0006] A first aspect of the present invention provides a method for preparing a dry-process electrode, the method comprising the following steps:
[0007] S1, mixing graphite, conductive carbon and an auxiliary binder to obtain a first mixed material;
[0008] S2, adding a main binder PTFE to the first mixed material under a temperature lower than the first temperature, performing a second stirring and mixing, to obtain a second mixed material;
[0009] S3, heating the second mixed material and performing a fiberization treatment to obtain a fiberized third mixture;
[0010] S4, rolling the third mixture through a hot rolling mill to form a mold, and compounding it onto a current collector to obtain the dry electrode sheet;
[0011] Wherein, the auxiliary binder is a high molecular polymer that swells 100%-200%.
[0012] Preferably, the auxiliary binder is one or more of P (VDF-HFP), styrene acrylic rubber, polyacrylates, and polymethyl methacrylate.
[0013] Preferably, the auxiliary binder is P(VDF-HFP), which is copolymerized from vinylidene fluoride (VDF) and hexafluoropropylene (HFP), has a particle size D50 of 7 μm, and a melting point of 100 to 180°C.
[0014] Preferably, in step S1, the mass ratio of the graphite, the conductive carbon and the auxiliary binder is (90-99.98):(0.01-5):(0.01-5).
[0015] Preferably, the mass ratio of the main binder PTFE added in step S2 to the auxiliary binder added in step S1 is 1:(0.3-1.5).
[0016] Preferably, the first stirring and mixing is performed in a planetary stirring tank, and the stirring time is 20 to 50 minutes.
[0017] Preferably, the second stirring and mixing is performed in a planetary stirring tank, the stirring condition is to keep the tank temperature below 15° C., and the stirring time is 1 to 3 hours.
[0018] Preferably, in step S3, the second mixed material is heated in an oven, the oven temperature is maintained at 90 to 120° C., and the heating is performed for 1 to 3 hours;
[0019] The heated second mixed material is placed in a high-speed disperser and dispersed for 3 to 8 minutes at a line speed of 25 to 40 m / s to perform fiberization treatment.
[0020] The second aspect of the present invention provides a dry-process electrode, which is manufactured using the method of the first aspect.
[0021] A third aspect of the present invention provides a secondary battery comprising the dry-process electrode according to the second aspect.
[0022] The beneficial effect of the present invention is that a new adhesive formula and material are used, the formula includes a main adhesive and an auxiliary adhesive, the auxiliary adhesive is a high molecular polymer that swells 100%-200%, and can significantly improve the wettability of the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0024] Figure 1 The figure is a comparison of the infiltration pictures of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] A first aspect of the present invention provides a method for preparing a dry electrode, the method comprising the following steps:
[0027] S1, mixing graphite, conductive carbon and an auxiliary binder to obtain a first mixed material;
[0028] S2, adding the main binder PTFE to the first mixed material under a temperature lower than the first temperature, performing a second stirring and mixing, to obtain a second mixed material;
[0029] S3, heating the second mixed material to the second temperature and then performing a fiberization treatment to obtain a fiberized third mixture;
[0030] S4, rolling the third mixture through a hot rolling mill to form a mold, and compounding it onto a current collector to obtain a dry electrode sheet;
[0031] The auxiliary binder is a high molecular polymer that swells by 100%-200%.
[0032] In some embodiments, the auxiliary binder is one or more of P(VDF-HFP), styrene-acrylic rubber, polyacrylate, and polymethyl methacrylate, wherein the particle size D50 of P(VDF-HFP) is less than 10 μm, and the melting point is 100-180°C.
[0033] In some embodiments, the auxiliary binder is P(VDF-HFP) with a particle size D50 of less than 10 μm and a melting point of 100-180° C. P(VDF-HFP) is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP).
[0034] In some embodiments, the auxiliary binder is P(VDF-HFP), which has a particle size D50 of 7 μm, a swelling rate of 120% in the electrolyte, and a melting point of 150°C.
[0035] In some embodiments, the mass ratio of graphite, conductive carbon and auxiliary binder in step S1 is (90-99.98):(0.01-5):(0.01-5).
[0036] In some embodiments, the mass ratio of the main binder PTFE added in step S2 to the auxiliary binder in step S1 is 1:(0.3-1.5).
[0037] In some embodiments, the first stirring and mixing is performed in a planetary stirring tank, and the stirring time is 20 to 50 minutes.
[0038] In some embodiments, the second stirring and mixing is performed in a planetary stirring tank, the stirring condition is to keep the tank temperature 15° C. lower than the first temperature, and the stirring time is 1 to 3 hours.
[0039] In some embodiments, in step S3, the second mixed material is heated in an oven to a second temperature of 90 to 120° C., and the oven temperature is maintained for 1 to 3 hours;
[0040] The heated second mixed material is placed in a high-speed disperser and dispersed for 3 to 8 minutes at a line speed of 25 to 40 m / s to perform a fiberization treatment.
[0041] The second aspect of the present invention provides a dry electrode made using the method of the first aspect.
[0042] A third aspect of the present invention provides a battery comprising the dry-process electrode according to the second aspect.
[0043] Example 1
[0044] 1) adding graphite, conductive carbon and P(VDF-HFP) into a planetary stirring tank in a mass ratio of 96:2:1, and dispersing for 30 minutes to obtain a first mixed material;
[0045] 2) adding PTFE so that the mass ratio of PTFE to P(VDF-HFP) is PTFE:P(VDF-HFP)=1:1, at which time the tank temperature is kept 15°C lower than the first temperature, and the stirring time is 2h to obtain a second mixed material;
[0046] 3) placing the second mixed material in an oven, maintaining the oven temperature at the second temperature of 100° C., heating for 2 hours, placing the heated second mixed material in a high-speed disperser at a linear speed of 30 m / s for 5 minutes, and performing a fiberization treatment to obtain a fiberized third mixture;
[0047] 4) The third mixture after the fiberization treatment is rolled into a mold by a hot rolling mill, and compounded with a current collector to obtain the dry electrode sheet.
[0048] Example 2
[0049] 1) adding graphite, conductive carbon and P(VDF-HFP) into a planetary stirring tank in a mass ratio of 96:2:0.5, and dispersing for 30 minutes to obtain a first mixed material;
[0050] 2) adding PTFE so that the mass ratio of PTFE to P(VDF-HFP) is PTFE:P(VDF-HFP)=1.5:0.5, at which time the tank temperature is kept 15°C lower than the first temperature, and the stirring time is 2h to obtain a second mixed material;
[0051] 3) placing the second mixed material in an oven, maintaining the oven temperature at the second temperature of 100° C., heating for 2 hours, placing the heated second mixed material in a high-speed disperser at a linear speed of 30 m / s for 5 minutes, and performing a fiberization treatment to obtain a fiberized third mixture;
[0052] 4) The third mixture after the fiberization treatment is rolled into a mold by a hot rolling mill, and compounded with a current collector to obtain the dry electrode sheet.
[0053] Example 3
[0054] 1) adding graphite, conductive carbon and P(VDF-HFP) into a planetary stirring tank in a mass ratio of 95:3:1, and dispersing for 30 minutes to obtain a first mixed material;
[0055] 2) adding PTFE of the same mass as P(VDF-HFP), i.e., PTFE:P(VDF-HFP)=1:1, at which time the tank temperature is kept 15°C lower than the first temperature, and the stirring time is 2h to obtain a second mixed material;
[0056] 3) placing the second mixed material in an oven, maintaining the oven temperature at the second temperature of 100° C., heating for 2 hours, placing the heated second mixed material in a high-speed disperser at a linear speed of 30 m / s for 5 minutes, and performing a fiberization treatment to obtain a fiberized third mixture;
[0057] 4) The third mixture after the fiberization treatment is rolled into a mold by a hot rolling mill, and compounded with a current collector to obtain the dry electrode sheet.
[0058] Example 4
[0059] 1) adding graphite, conductive carbon and P(VDF-HFP) into a planetary stirring tank in a mass ratio of 95:2:2, and dispersing for 30 minutes to obtain a first mixed material;
[0060] 2) adding PTFE so that the mass ratio of PTFE to P(VDF-HFP) is PTFE:P(VDF-HFP)=1:2, at which time the tank temperature is kept 15°C lower than the first temperature, and the stirring time is 2h to obtain a second mixed material;
[0061] 3) placing the second mixed material in an oven, maintaining the oven temperature at the second temperature of 100° C., heating for 2 hours, placing the heated second mixed material in a high-speed disperser at a linear speed of 30 m / s for 5 minutes, and performing a fiberization treatment to obtain a fiberized third mixture;
[0062] 4) The third mixture after the fiberization treatment is rolled into a mold by a hot rolling mill, and compounded with a current collector to obtain the dry electrode sheet.
[0063] Example 5
[0064] 1) adding graphite, conductive carbon and P(VDF-HFP) into a planetary stirring tank in a mass ratio of 92:2:5, and dispersing for 30 minutes to obtain a first mixed material;
[0065] 2) adding PTFE so that the mass ratio of PTFE to P(VDF-HFP) is PTFE:P(VDF-HFP)=1:5, at which time the tank temperature is kept 15°C lower than the first temperature, and the stirring time is 2h to obtain a second mixed material;
[0066] 3) placing the second mixed material in an oven, maintaining the oven temperature at the second temperature of 100° C., heating for 2 hours, placing the heated second mixed material in a high-speed disperser at a linear speed of 30 m / s for 5 minutes, and performing a fiberization treatment to obtain a fiberized third mixture;
[0067] 4) The third mixture after the fiberization treatment is rolled into a mold by a hot rolling mill, and compounded with a current collector to obtain the dry electrode sheet.
[0068] Comparative Example 1
[0069] 1) adding graphite and conductive carbon in a mass ratio of 96:2 into a planetary stirring tank and dispersing for 30 minutes to obtain a first mixed material;
[0070] 2) adding PTFE so that the mass ratio of PTFE to graphite and conductive carbon is 2:96:2, at which time the tank temperature is kept 15° C. lower than the first temperature, and the stirring time is 2 h to obtain a second mixed material;
[0071] 3) placing the second mixed material in an oven, maintaining the oven temperature at the second temperature of 100° C., heating for 2 hours, placing the heated second mixed material in a high-speed disperser at a linear speed of 30 m / s for 5 minutes, and performing a fiberization treatment to obtain a fiberized third mixture;
[0072] 4) The third mixture after the fiberization treatment is rolled into a mold by a hot rolling mill, and compounded with a current collector to obtain the dry electrode sheet.
[0073] Related data testing
[0074] The pole pieces in the above-mentioned embodiments and comparative examples were tested for the relevant items listed in Table 1.
[0075] The electrolyte infiltration rate was measured by capillary method, and the infiltration pictures of the embodiments and comparative examples were recorded.
[0076] Capillary test method
[0077] Take the pole piece (control compaction and surface density) and lay it flat;
[0078] Take the capillary tube to absorb the electrolyte and record the height of the electrolyte level;
[0079] Place the capillary tube vertically on the stage after liquid absorption, and let it stand for 100 seconds to allow the electrolyte to fall freely;
[0080] Record the electrolyte level.
[0081] Figure 1 Comparison of electrolyte infiltration images of the electrode pieces of Example 1 and Comparative Example 1.
[0082] like Figure 1 As shown, by comparing Example 1 and Comparative Example 1, it is found that when the electrolyte is dripped onto the dry electrode by the capillary method, in Example 1, it diffuses quickly after 30 seconds, the immersion trace is shallow after 1 minute, and basically dissipates after 5 minutes; while Comparative Example 1 diffuses slowly, and there are still obvious traces after 5 minutes.
[0083] Table 1 is the data of electrolyte infiltration rate measured by capillary method for the embodiments and comparative examples.
[0084] sample Liquid level drop height in 100s / mm Example 1 36 Example 2 23 Example 3 38 Example 4 45 Example 5 65 Comparative Example 1 5
[0085] Table 1
[0086] The electrode was made according to the above-mentioned embodiment and comparative example method, and the electrolyte wettability was tested by the capillary method. The data of the height of the electrolyte level falling in 100 seconds in the capillary was obtained. The larger the value, the better the wettability. It can be seen that the value of the embodiment is significantly higher than that of the comparative example.
[0087] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a dry electrode, characterized in that: The steps include: S1, stirring and mixing graphite, conductive carbon and auxiliary binder to obtain a first mixed material; S2, adding a main binder PTFE to the first mixed material at a temperature lower than the first temperature, performing a second stirring and mixing, to obtain a second mixed material; S3, heating the second mixture to a second temperature and then performing a fiberization treatment to obtain a fiberized third mixture; S4, rolling the third mixture through a hot rolling mill to form a mold, and compounding it onto a current collector to obtain the dry-process electrode sheet; Wherein, the auxiliary binder is a high molecular polymer that swells 100%-200%.
2. The preparation method according to claim 1, wherein The auxiliary binder is any one of P(VDF-HFP), styrene acrylic rubber, polyacrylates, and polymethyl methacrylate, or a combination of at least two of them in any proportion.
3. The preparation method according to claim 1-2, characterized in that The auxiliary binder is P (VDF-HFP), the particle size D50 of which is less than 10 μm and the melting point is 100-180° C.
4. The preparation method according to claim 1, wherein The mass ratio of the graphite, conductive carbon and auxiliary binder in step S1 is (90-99.98):(0.01-5):(0.01-5).
5. The preparation method according to claim 1, wherein The mass ratio of the main binder PTFE added in step S2 to the auxiliary binder added in step S1 is 1:(0.3-1.5).
6. The preparation method according to claim 1, wherein In step S1, the first stirring and mixing is performed in a planetary stirring tank, and the stirring time is 20 to 50 minutes.
7. The preparation method according to claim 1, wherein In step S2, the first temperature is less than 15° C., and the stirring time is 1 to 3 hours.
8. The preparation method according to claim 1, wherein In step S3, the second mixed material is heated to a second temperature of 90 to 120° C. for 1 to 3 hours; The fiberization treatment in step S3 is carried out in a high-speed disperser for 3 to 8 minutes, maintaining a linear speed of 25 to 40 m / s.
9. A dry electrode, characterized in that: The dry-process electrode is prepared by the method according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: Including the dry electrode described in claim 9.
Citation Information
Patent Citations
Preparation method of dry-method electrode plate and secondary battery
CN114759158A
Method for preparing high-load pre-lithiation negative electrode based on dry method
CN117577788A
Manufacturing method of non-contact automotive fuel level sensor
KR102166571B1
Self-supporting electrode membrane, secondary battery and device
WO2024198543A1
Cited By
Preparation method of solid anode strip with high stability and low interface impedance
CN121076080A